Удосконалення технології червоного напівсухого вина - Гобан, Юрій Васильович; Hoban, Yurii Vasylovych (Національний університет "Львівська політехніка", 2024)
В магістерській кваліфікаційній роботі опрацьовано важливу задачу удосконалення технології одержання червоних напівсухих столових виноматеріалів. Розглянуто сучасний стан виноробства та особливості виробництва виноградних вин у різних країнах світу. Акцентовано увагу на загальносвітових тенденцій розвитку виноградарства і виноробства. Розглянуто існуючі способи та особливості одержання червоних столових вин. Здійснено аналіз асортименту вітчизняних червоних столових вин. Охарактеризовано найкращі червоні напівсухі столові вина, які виготовляються виноробними підприємствами України. Відзначено особливості хімічного складу червоних столових вин та їх фізіологічні, профілактичні, лікувальні та дієтичні властивості. Підсумовано, що, виноградне вино, особливо червоне, у невеликих кількостях корисне для організму людини, має лікувально-профілактичну дію. Корисна дія вина проявляється тільки за низьких концентрацій спирту, у невеликих його дозах, у поєднанні з іншими харчовими продуктами. Для одержання червоного столового напівсухого вина використовували виноград червоних сортів, вирощений в грунтово-кліматичних умовах Прикартаття, які характеризуються помірно-теплим кліматом. Наведено методики проведення досліджень та методики аналізів. Досліджено динаміку спиртового бродіння виноградного сусла шести сортів червоного винограду, а саме: Каберне Совіньойн, Каберне Кортіс, Каберне Дорса, Сіра, Лівадійський чорний та Ізабела. Встановлено, що практично повне зброджування цукрів виноградного сусла досягається впродовж 7 діб при проведенні бродіння за температури 20 оС. При цьому одержуються сухі столові виноматеріалі із вмістом етилового спирту від 9,8 до 12,1 %об, що відповідає вимогам Технологічної інструкції. Надалі ці виноматеріали використовували у купажі із консервованим виноградним суслом для одержання напівсухого столового вина. Кількість консервованого сусла визначали виходячи із кондиційності готового червоного столового напівсухого вина, яке повинно містити до 2,5 г/100 см3 цукру. Консервоване сусло одержували пастеризацією освітленого сусла із винограду сорту Каберне Кортіс з цукристістю 20 г/100 см3, яку проводили за температури 60 оС. Відтак після охолодження до 25 оС пастеризоване сусло сульфітували до загального вмісту SO2, що дорівнює 250 мг/дм3. Якість одержаних вин оцінювали за результатами органолептичного аналізів. Оцінку у 7 балів і вище, яка вказує на задатки розвитку хорошої якості у молодих винах, одержали взірці чотирьох вин із винограду сортів Каберне Кортіс, Каберне Дорса, Каберне Совіньйон та Лівадійський чорний. Досліджувані взірці готових напівсухих вин також аналізували на вміст цукру, спирту та титрованих кислот. Згідно одержаних результатів усі вина за кондиціями відповідають нормам. Найвищий вміст спирту та цукру є у взірцях вин Лівадійський чорний, Каберне Кортіс і Каберне Дорса. Найнижчу титровану кислотність має вино із винограду сорту Каберне Кортіс. Встановлено, за результатами досліджень найкращі результати щодо якості та кондиційності вина забезпечує виноград сорту Каберне Кортіс. Розроблено технологічну схему процесу одержання напівсухого червоного столового вина. Приведено норми технологічного режиму процесу. Проведено розрахунок продуктів та складено матеріальний баланс процесу. Розраховану витрату сировини і матеріалів. Також розраховано витрати на проведення лабораторних досліджень у межах магістерської кваліфікаційної роботи в лабораторії кафедри технології органічних продуктів. Загальний кошторис витрат для даного дослідження становить 92606,2 грн. Накладні витрати становлять 17923,8 грн. Економічний ефект проведених досліджень буде досягнуто за рахунок використання дешевої сировини, яка вирощена у західному регіоні України та розширення асортименту напівсухих столових вин. Метою магістерської кваліфікаційної роботи є дослідження процесу одержання червоного столового напівсухого вина із винограду, вирощеного в умовах західного регіону України. Об’єкт дослідження – технологія одержання червоних столовин виноградних вин. Предмет дослідження – процес одержання виноматеріалу бродінням виноградного сусла з червоних сортів винограду та його використання у виробництві столового червоного напівсухого вина. Методи досліджень: експериментальні (хімічні – визначення вмісту цукрів, етилового спирту, кислотності вин, органолептиний – дегустаційна оцінка якості одержаних вин).

The master's qualification work deals with the important task of improving the technology for obtaining red semi-dry table wine materials. The current state of winemaking and the features of grape wine production in different countries of the world are considered. Attention is focused on global trends in the development of viticulture and winemaking. The existing methods and features of obtaining red table wines are considered. The range of domestic red table wines is analyzed. The best red semi-dry table wines produced by Ukrainian wineries are characterized. The features of the chemical composition of red table wines and their physiological, prophylactic, therapeutic and dietary properties are noted. It is concluded that grape wine, especially red, in small quantities is useful for the human body, has a therapeutic and prophylactic effect. The beneficial effect of wine is manifested only at low concentrations of alcohol, in small doses, in combination with other food products. To obtain red semi-dry table wine, red grapes grown in the soil and climatic conditions of Prykartattya, which are characterized by a moderately warm climate, were used. Research methods and analysis methods are presented. The dynamics of alcoholic fermentation of grape must of six varieties of red grapes, namely: Cabernet Sauvignon, Cabernet Cortis, Cabernet Dorsa, Syrah, Livadia Black and Isabella, were studied. It was found that almost complete fermentation of grape must sugars is achieved within 7 days when fermentation is carried out at a temperature of 20 ° C. In this case, dry table wine materials with an ethyl alcohol content of 9.8 to 12.1% vol are obtained, which meets the requirements of the Technological Instructions. Later, these wine materials were used in a blend with canned grape must to obtain semi-dry table wine. The amount of canned must was determined based on the condition of the finished red table semi-dry wine, which should contain up to 2.5 g/100 cm3 of sugar. Preserved must was obtained by pasteurization of clarified must from Cabernet Cortis grapes with a sugar content of 20 g/100 cm3, which was carried out at a temperature of 60 ° C. Then, after cooling to 25 ° C, the pasteurized must was sulfidated to a total SO2 content of 250 mg/dm3. The quality of the resulting wines was assessed according to the results of organoleptic analysis. A score of 7 points and above, which indicates the development of good quality in young wines, was obtained by samples of four wines from the Cabernet Cortis, Cabernet Dorsa, Cabernet Sauvignon and Livadia Black grapes. The studied samples of finished semi-dry wines were also analyzed for the content of sugar, alcohol and titrated acids. According to the results obtained, all wines meet the standards in terms of conditions. The highest alcohol and sugar content is found in the Livadia Black, Cabernet Cortis, and Cabernet Dorsa wine samples. The lowest titrated acidity is found in wine made from Cabernet Cortis grapes. t was established that, according to the results of the research, the best results in terms of quality and condition of wine are provided by Cabernet Cortis grapes. A technological scheme for the process of obtaining semi-dry red table wine has been developed. The norms of the technological regime of the process have been given. The calculation of products has been carried out and the material balance of the process has been drawn up. The consumption of raw materials and materials has been calculated. The costs of conducting laboratory research within the framework of the master's qualification work in the laboratory of the Department of Organic Products Technology have also been calculated. The total cost estimate for this research is 92,606.2 UAH. Overhead costs are 17,923.8 UAH. The economic effect of the research will be achieved through the use of cheap raw materials grown in the western region of Ukraine and the expansion of the range of semi-dry table wines. The purpose of the master's qualification work is to study the process of obtaining red table semi-dry wine from grapes grown in the conditions of the western region of Ukraine. The object of the study is the technology of obtaining red table grape wines. The subject of the study is the process of obtaining wine material by fermentation of grape must from red grape varieties and its use in the production of red semi-dry table wine. Research methods: experimental (chemical - determination of the content of sugars, ethyl alcohol, acidity of wines, organoleptic - tasting assessment of the quality of the obtained wines).
Improvement of red semi-dry wine technology
Keywords: 3.181.00.00; спиртове бродіння; виноград; виноматеріал; виноградне сумло; червоне напівсухе вино; alcoholic fermentation; grapes; wine material; grape marc; red semi-dry wine